Time perception of emotional videos - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
It is known that accuracy of time estimation depends on time perception and it is affected by various internal and external factors. However, it is a field that there is a few research on exploration of neurophysiological basis of this relations. These limited number of studies are found to be designed based on basic and static stimuli. On the other hand, time percpetion in real life stiuaion requires dealing with more complex and a number of stimuli. This study aims to identify effect of emotion on time estimation processes and electrophysiological basis of this relationship while using more complex stimuli. Emotional motion videos which are chosen from IMDB movies are used in this study to crate emotional effect on subjects. It is found that complex stimuli cause disruption of time perception while there was no difference between emotional categories of videos. © 2017 IEEE.
Keywords: EEG; emotion; time perception